Temperature, humidity and weather conditions at Vernadsky Station in 2012 - V. F. Martazinova; E. K. Ivanova; V. E. Tymofeev (Ukrainian Antarctic Journal, 2013)
The description of the temperature regime in 2012 by months is compared to historical averages and modern weather conditions. Abnormal weather conditions are observed during the winter 2012, when monthly mean temperatures in July and August exceeded historical averages (1996–2010) and monthly precipitation exceeded multi-years’ norm by almost 1.5 times. Summer season in 2012 was cold enough, the monthly mean temperatures in January and February were below historical averages; in January the excess of precipitation, and in February – deficit of precipitation has been registered. New predominant types of atmospheric circulation are identified in January-February, which supplemented archive of the etalon synoptic patterns obtained earlier for the 1991–2000.